Học bằng các mô hình mạng neural - Vũ Thanh Nguyên (Journal of Technical Education Science, 2006)
This paper mentions about neural network models for learning as backpropogation neural network model, radial basis function neural network model, recurrent fuzzy neural network… These models are applied to learn and train on recognition, to analyse and to forecast for investment, finance, optimization, to evaluate for development on agriculture, industry, oriented to develop market, to set up business model…